Incidence and Risk Factors for Early Postoperative Arrhythmias in Congenital Heart Disease – Systematic Review - Mayaya Petra-Caroline; Tinică Grigore; Chistol Raluca Ozana; Moraru Liviu; Damian Simona Irina; Frăsinariu Otilia Elena; Furnica Cristina (Journal of Cardiovascular Emergencies)
Postoperative arrhythmias are commonly seen in pediatric cardiac intensive care units and are linked to higher rates of both morbidity and mortality in children with congenital heart disease. However, the incidence of early postoperative arrhythmias in the pediatric population is unclear, varying from 7.3% to 48% in the literature. We searched the PubMed, Embase, and Web of Science databases from 2000 to 2025 with the aim to perform a systematic review of the existing literature on the incidence and risk factors of early arrhythmias following heart surgery. A total of 16 cross-sectional observational studies, including 5,563 patients who underwent surgery for congenital heart disease and 901 patients who developed early postoperative arrhythmias, met the inclusion criteria. Patients developing early postoperative dysrhythmias were younger, with a lower body weight, and the duration of cardiopulmonary bypass was significantly longer. Other incriminated risk factors for the occurrence of early postoperative arrhythmias were hemodynamic instability, complexity of the surgical procedure, and higher vasoactive-inotropic scores. Pediatric patients with congenital heart disease who undergo cardiac surgery face increased morbidity and mortality due to the risk associated with the multifactorial complication of early postoperative arrhythmias. The reported incidence of these arrhythmias varies greatly among different studies and a better understanding of risk factors and pathophysiological mechanisms would improve postoperative outcomes for this notably exposed population.